Aeromonas salmonicida infection kinetics and protective immune response to vaccination in sablefish (Anoplopoma fimbria). Issue 104 (September 2020) - Vasquez, Ignacio; Cao, Trung; Hossain, Ahmed; Valderrama, Katherinne; Gnanagobal, Hajarooba; Dang, My; Leeuwis, Robine H.J.; Ness, Michael; Campbell, Briony; Gendron, Robert; Kao, Kenneth; Westcott, Jillian; et al.
Abstract: Effective vaccine programs against Aeromonas salmonicida have been identified as a high priority area for the sablefish ( Anoplopoma fimbria ) aquaculture. In this study, we established an A. salmonicida infection model in sablefish to evaluate the efficacy of commercial vaccines and an autogenous vaccine preparation. Groups of 40 fish were intraperitoneally (ip) injected with different doses of A. salmonicida J410 isolated from infected sablefish to calculate the median lethal dose (LD50 ). Samples of blood, head kidney, spleen, brain, and liver were also collected at different time points to determine the infection kinetics. The LD50 was estimated as ~3 × 10 5 CFU/dose. To evaluate the immune protection provided by an autogenous vaccine and two commercial vaccines in a common garden experimental design, 140 fish were PIT-tagged, vaccinated and distributed equally into 4 tanks (35 fish for each group, including a control group). Blood samples were taken every 2 weeks to evaluate IgM titers. At 10 weeks post-immunization, all groups were ip challenged with 100 times the calculated LD50 for A. salmonicida J410. A. salmonicida was detected after 5 days post-infection (dpi) in all collected tissues. At 30 days post-challenge the relative percentage survival (RPS) with respect to the control group was calculated for each vaccine. The RPS for the bacterin mix was 65.22%, for Forte Micro 4® vaccine was 56.52% and for Alpha Ject Micro 4® was 30.43%, and these RPS values were reflected by A. salmonicida tissue colonization levels at 10 days post-challenge. Total IgM titers peaked at 6–8 weeks post-immunization, where the autogenous vaccine group showed the highest IgM titers and these values were consistent with the RPS data. Also, we determined that the A. salmonicida A-layer binds to immunoglobulins F(ab)' in a non-specific fashion, interfering with immune assays and potentially vaccine efficacy. Our results indicate that vaccine design influences sablefish immunity and provide a guide for future sablefish vaccine programs. Highlights: We developed an infection model for sablefish, including determining the LD50 dose for atypical A. salmonicida (~3x10 5 CFU/dose). Atypical A. salmonicida J410 does causes a chronic type of infection that involves colonization of the brain. The monovalent autogenous vaccine mix using three A. salmonicida strains provided better protection than two polyvalent commercial vaccines. Vaccine immune protection was associated with the IgM titers, where the autogenous vaccinated fish had the highest RPS and IgM titers. The A. salmonicida A-layer binds to immunoglobulins in a non-specific fashion, questioning its utility as an immune protective antigen.